Пізньопалеолітична стоянка Галич І (попередні результати досліджень) - Ситник, О.С.; Цирек, К. (Археологія, 2002)
Публікація містить інформацію про археологічні дослідження однієї з цікавих і перспективних пам'яток пізнього палеоліту Верхнього Подністров'я — стоянки Галич І. Подано узагальнений аналіз крем'яного матеріалу, зроблено припущення про належність пам'ятки до східнограветтської подністровської традиції. В 2000 г. начаты археологические раскопки позднепалеолитической стоянки Галич І (правый берег Днестра), которые проводятся совместной Украинско-Польской экспедицией. Культурный слой залегает в верхней части плейстоценовых лессов («ровенский горизонт» — аналог Ляско). Исследовано 75 м2 площади, на которой зафиксировано два интенсивных скопления костей мамонта (более 90% всех фаунистических остатков). Кремневых изделий мало — 236 экз. Имеются призматические пирамидальные, торцевые нуклеусы, орудия труда (резцы, скребки). В предварительном плане эти материалы сравниваются с инвентарем Межигорцев І и относятся к «днестровской традиции» восточного граветта (эпиграветта). In 2000 the joint Ukraine-Polish expedition started the archaeological excavations of the Late Paleolithic site Halych-I (the right bank of the Dniester river). The cultural fayer is localized in the upper part of Pleistocene loesses («Rivne horizon» analogical to Lasco), On the explored area of 75 m2, two intensive accumulations of mammoth bones (more than 90 % of all the faunal remains) were fixed. The layer is very poor. The total number of flint articles is 236.
The collection consists of prismatic and pyramidal cores, cores for bladelets, and 0013 (burins, scrapers). In the preliminary plan, these materials are chronologically close to the accessory of the Upper Paleolithic horizon of Mezhygortsy-I (the left Dniester bank) and belong to the «Dniester tradition» of the Eastern Gravette (Epi-Gravette).